Increasing the Knowledge of High School Biology Teachers on the Preservation of Pediculus humanus capitis in Preparat Glass - Fandi Tuju; Mirnawati Dewi; Febri Nur Ngazizah; Desimaria Panjaitan; Decenly Decenly (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Pediculus humanus capitis (head lice) is an obligate ectoparasite. Preparation of specimens is a procedure carried out to accurately preserve, identify, and analyze head lice. The Palangka Raya Biology Teachers Forum (MGMP) has collaborated with the Community Service Team of the Biology Study Program. This activity aims to improve high school Biology teachers' skills in preserving Pediculus humanus capitis (morphological observation and identification). This provides a solution to make school laboratory practicals more attractive, as preserved specimens can be stored and used long-term. The activity was offline at the PPIIG Building Laboratory, Palangka Raya University, in August 2023. The activity included lectures, discussions, training, and pre-test and post-test evaluation. The evaluation results show an increase in scores after the training, with an average pre-test score of 50.00 increasing to 80.33 in the post-test. It can be concluded that participants' knowledge increased after attending this training.